L-F001, a Multifunctional Fasudil-Lipoic Acid Dimer Prevents RSL3-Induced Ferroptosis via Maintaining Iron Homeostasis and Inhibiting JNK in HT22 Cells - Peng, Weijia; Ouyang, Ying; Wang, Shuyi; Hou, Jiawei; Zhu, Zeyu; Yang, Yang; Zhou, Ruiyu; Pi, Rongbiao (Frontiers in Cellular Neuroscience, 2022)
Ferroptosis, a new type of programmed cell death and growing studies demonstrated that ferroptosis induces and aggravates cerebral ischemia. Ras-selective lethality 3 (RSL3), is a Glutathione peroxidase 4 (GPX4) inhibitor and ferroptosis inducer. Here, we investigated the protective effect of L-F001, a novel fasudil-lipoic acid dimer against RSL-3-induced ferroptosis HT22 cells. L-F001 effectively protected RSL3-induced in a concentration dependent manner and significantly attenuated lipid peroxidation. Meanwhile, L-F001 could restore GPX4 and glutamate-cysteine ligase modifier subunit (GCLM) levels, and significantly restored iron homeostasis. Finally, L-F001 could reduce RSL3-induced c-Jun N-terminal kinase (JNK) activation, which plays important roles in ferroptosis. Taken together, our results showed that L-F001 might be a multi-target agent for the therapy of ferroptosis-related diseases, such as cerebral ischemia.